Features of Adaptation of International Financial Reporting Standards in the Russian Commercial Organizations - Duvanskaya, Nina A.; Sverchkova, Ol’ga F. (International Journal of Economics and Financial Issues, 2016)
In connection with the crisis increased the urgency of adaptation to international standards of financial reporting in the Russian economy in the Russian commercial organizations. Great influence on the modern accounting in Russia have been successfully carried out reforms and existing requirements for a number of commercial organizations on the preparation of financial statements in accordance with International Financial Reporting Standards (IFRS). The article shows that the accounting system in the Russian Federation for the period of market reforms has undergone significant changes, and the basic steps of the translation of the Russian system of accounting and reporting in IFRS format. The article identified and grouped the main problems of further development of Russian accounting and reporting. Showing difficulties that do not allow to apply international standards in full, as well as proposed solutions to these problems. As one of these solutions to the identified problems proposed structure of the conceptual foundations of accounting (financial) statements of the private sector of the Russian Federation, the sequence recommended approval of federal accounting and reporting standards for commercial organizations in Russia. Keywords: International financial reporting standards, Russian accounting system, a commercial organization JEL Classifications: F37, F38, G10